Infant and Young Child Feeding Practices Among Chepang Community, Chitwan - Luitel, Iswari; Ban, Rita Kumari; Munikar, Sabika (Medical Journal of Shree Birendra Hospital, 2020)
Introduction: Infant and young child feeding practices play vital role for the growth and development. It is recommended to exclusively breastfed for first six months and thereafter receive complementary foods with continued breastfeeding. However Chepang, the indigenous community of Nepal depends primarily upon forest food. This study aims to determine the infant and young child feeding practices among Chepang children. Methods: A cross sectional study was conducted among the mothers of 77 children aged six to 59 months through purposive sampling. Data was collected through face to face interview taking informed written consent. The collected data were analysed for descriptive and bivariate analysis using SPSS version 21. Results: In this study, mean age of respondents was 25.92 (±7.04) years, 68.8% followed Christian religion, 51.9% were educated, only 45.5% of respondent’s spouse were educated and 51.9% belonged to nuclear family. Among the respondents, 65.7% had good breast feeding practice and 88.3% had good complementary feeding practice. Statistically significant relationship was found between breast feeding practice and educational status and also between complementary feeding practice and family type. Conclusions: This study found that respondents had good breast feeding practice and complementary feeding practice. Among the respondent, seven out of 10 had good breast feeding practice and nine out of 10 had good complementary feeding practice. Association between breast feeding practice and educational status puts light upon the need for educating and empowering women for improved infant and young child feeding practices.